Initiation of lumen formation from junctions via differential actomyosin contractility regulated by dynamic recruitment of Rasip1 - Jianmin Yin; Niels Schellinx; Ludovico Maggi; Kathrin Gundel; Cora Wiesner; Maria Paraskevi Kotini; Minkyoung Lee; Li-Kun Phng; Heinz-Georg Belting; Markus Affolter (Nature Communications)
Abstract De novo lumen formation necessitates the precise segregation of junctional proteins from apical surfaces, yet the underlying mechanisms remain unclear. Using a zebrafish model, we develop a series of molecular reporters, photo-convertible and optogenetic tools to study the establishment of apical domains. Our study identifies Rasip1 as one of the earliest apical proteins recruited, which suppresses actomyosin contractility at junctional patches by inhibiting NMII, thereby allowing for the sustained outward flow of junctional complexes. Following the establishment of apical compartments, Rasip1 shuttles between junctions and the apical compartments in response to local high tension. Rasip1 confines Cdh5 to junctions by suppressing apical contractility. Conversely, the recruitment of Rasip1 to junctions is regulated by Heg1 and Krit1 to modulate contractility along junctions. Overall, de novo lumen formation and maintenance depend on the precise control of contractility within apical compartments and junctions, orchestrated by the dynamic recruitment of Rasip1.